DESIGN AND OPTIMIZATION OF A SUSTAINABLE CLOSED LOOP SUPPLY CHAIN NETWORK (SCLSCN) SCLSCN): A MULTI PRODUCT, MULTI ECHELON MULTI MODAL TRANSPORT AND MULTI PLANT TECHNOLOGY CONDITIONS - Victor Jinn; Harold Ugochukwu Nwosu; Shadrach Matthew Uzoma (International Journal of Innovations in Engineering Research and Technology, 2023)
A mixed integer mathematical model that concurrently optimizes the three intrinsic aspects of sustainability : cost, environmental effect, and social impact , was created for a general closed loop supply chain network. The suggested innovative hybrid model is developed to incorporates several real world aspects of SC execution, such as multi product, multi echelons, multiple production technology, and multiple means of transportation. On the GAMS/CPLEX solver, the weighted sum method is employed to solve that model after carrying out AHP to determine the weights assigned to objectives. In order to verify the accuracy of the suggested model, a case study was carried out in the context of an automotive SCND in Nigeria. The result demonstrates that model is capable of planning the SCLSCN.